Fatal, Non-Fatal Injuries, and Deaths Resulting from Traffic Accidents for the Years 2018-2023 in Iraq - Mohammed, Anaam; Alkhudhairy, Miaad K.; Aldhalemi, Ali A. (Medical Science Journal for Advance Research, 2025)
The recording of road traffic accidents (RTAs) data by the relevant ministries with high transparency provides a roadmap that enables the state to manage RTAs and develop solutions that reduce loss of life and mitigate health and economic burdens. Therefore, the study aimed to evaluate the recording of RTAs and their consequences, including road traffic injuries (RTIs) and road traffic deaths (RTDs) in the Iraqi Ministry of Health (IMH) and Iraqi Ministry of Planning (MoP) over a six-year period from 2018 to 2023. The data of this cross-sectional study were collected from the Central Statistical Organization (CSO) of the MoP and IMH. The statistical analysis of data was done using the Statistical Package for Social Sciences (SPSS). According to MoP, the highest percentage of RTAs in the years 2022 and 2023 was 18.5%, while the lowest percentage was 13.1% for the year 2020. Iraq recorded the highest percentage of RTDs estimated at 18.4% for the years 2022 and 2023, while the lowest RTDs percentage, at 12%, was recorded in 2022. The MoP data and shows an upward trend in RTIs from 2018 to 2023, except for 2020, which showed an exceptionally low percentage which was estimated at 12.6%. Among other indicators, it was noted that the year 2022 recorded 19.0%, which was the highest percentage of RTIs, followed by the year 2023, in which the percentage of RTIs reached 18.5%. According to IMH statistics, the year 2018 and 2019 recorded a percentage of 44.5%, Remarkably, the lowest percentage of fatal RTIs was 38.3% in the year 2020. The highest percentage of RTIs was recorded in the year 2021, at 59.3%, On the other hand, the lowest percentage of RTIs was documented, at 51.8%. Statistically, there was a relative difference in RTDs recorded between the IMH and MoP, ranging between 67.9 and 93.3%. The percentage in 2020 was estimated at 101.7%, with an extreme significant difference of P=0.0001. There was a relative difference in recorded RTIs between the IMH and MoP, ranging between 223.6 and 591.8, with a very significant difference of P=0.0025. Hence, it is imperative to consider the possibility of studying and analyzing some of the data recorded by the IMH and MoP assessing the reliability and transparency of documentation and recording, and enabling stakeholders to understand this serious issue, which continues to cause confusion regarding the true traffic accidents profile Unifying, updating and monitoring documentation sources will constitute a positive turning point in the credibility and reliability of national traffic accident registration systems, in order to formulate a systematic strategy to address what can be addressed according to available capabilities.